Comparison evaluation of bacterial DNA extraction methods for improved molecular diagnostic accuracy of sepsis-causing pathogens in clinical whole blood samples - Byungjoon Na; Junghun Park; Sojin Park; Eunseon Park; Jimin Jang; Yu-Hee Kim; Jinyeop Lee; Hae-Sun Chung (Scientific Reports)
Abstract Sepsis, a leading cause of mortality, requires rapid and accurate pathogen identification to ensure effective treatment. Current diagnostic methods such as blood cultures are time-consuming, whereas molecular diagnostic techniques represent a promising alternative for faster pathogen detection. Therefore, the aim of this study was to evaluate different DNA extraction methods for the improved detection of infectious pathogens in the bloodstream. Specifically, we compared one column-based DNA extraction method (QIAamp DNA Blood Mini Kit) with two magnetic bead-based DNA extraction methods (K-SL DNA Extraction Kit and GraBon™ system). Real-time PCR was performed using specific primers to assess the efficiency of each method. The K-SL DNA Extraction Kit and GraBon™ system exhibited higher accuracy rates of 77.5% (22/40) and 76.5% (21/40), respectively, compared to the QIAamp DNA Blood Mini Kit, which had an accuracy rate 65.0% (12/40) for Escherichia coli detection, whereas the GraBon™ system demonstrated higher accuracy rate of 77.5% (22/40) than the other two methods, which had an accuracy rates of 67.5% (14/40) for Staphylococcus aureus detection. All methods displayed high specificity for negative samples (100%). These findings highlight the superior performance of magnetic bead-based methods, particularly when automated, for extracting bacterial DNA from whole blood samples. Such methods may enable the more rapid and accurate diagnosis of bloodstream infections, potentially improving patient outcomes.